High Throughput Detection of 327 Drugs in Blood by LC–MS-MS with Automated Data Processing - Di Rago, Matthew; Pantatan, Supranee; Hargreaves, Melynda; Wong, Katherine; Mantinieks, Dylan; Kotsos, Alex; Glowacki, Linda; Drummer, Olaf H; Gerostamoulos, Dimitri (Journal of analytical toxicology, 2021)
The described procedure provides a rapid technique for the detection and semi-quantitation of a large number of drugs in blood. This procedure uses a minimal sample volume and employs a one-step liquid extraction and automated data processing to yield rapid turnaround times. A total of 327 of the most commonly used medicinal and illicit drugs in Australia were selected including various amphetamines, anesthetics, antidepressants, antipsychotics, anticonvulsants, benzodiazepines, beta blockers, opioid and nonopioid analgesics, stimulants, THC and a large number of synthetic cannabinoids and other novel psychoactive substances. The extracts were subject to 5-minute chromatography using a Kinetex C18 50 × 4.6 mm 2.6 μm solid-core analytical column and analyzed using a Sciex 3200 Q-TRAP MS-MS (+ ESI, MRM mode, two transitions per analyte). The method was fully validated in accordance with international guidelines. Matrix effects and extraction efficiencies were acceptable with most analytes showing > 80% response and low variation (within 25%RSD). Cannabinoids were most affected by the matrix and yielded poorest recovery values but were still detectable. Precision, accuracy, repeatability and multipoint linearity were assessed for all analytes. The method has been used in routine practice in the forensic toxicology service at the Victorian Institute of Forensic Medicine in over 6000 coronial investigations using both postmortem and clinical blood specimens. This technique has greatly increased throughput, reduced turnaround times and allowed for rapid same-day analysis of results when needed. The method is routinely used in routine overnight testing with results reported to pathologists within 4 h of data acquisition. This rapid toxicological technique is used in conjunction with other investigative processes such as full-body CT imaging, review of case circumstances and medical histories to provide an efficient death investigation process.